Partial melting of amphibolitic lower crust and subsequent melt-crystal separation for generation of the Early Eocene magmatism in eastern Himalaya - Dai, Zuowen; Yang, Zhiming; Li, Guangming; Xie, Yuling; Dong, Lei; Gao, Ke; Cao, Huawen (Frontiers in Earth Science, 2023)
The Himalayan leucogranites provide good opportunity to investigate the crustal evolution in the southern Qinghai-Tibet Plateau. In this study, we present monazite U-Th-Pb and zircon U-Pb ages, zircon Hf and whole-rock Sr-Nd-Pb isotopic and whole-rock major and trace element compositions for the Liemai two-mica granite, southeastern Yardoi dome. Together with previously published data we revalued the petrogenesis of the Early Eocene magmatism in this region and its geological implications. The zircon and monazite U-(Th)-Pb dating showed that the Liemai two-mica granite was generated at ~43 Ma, similar to other Early Eocene granites in the Yardoi area (Yardoi, Dala, Quedang two-mica granite, Riang subvolcanic rocks and Yardoi leucogranite). Geochemically, the Liemai two-mica granite, similar to other coeval two-mica granites in the Yardoi area, have relatively high Sr/Y and LaN/YbN ratios (showing adakitic features) and MgO and Mg# values compared to the Riang subvolcanic rocks and Yardoi leucogranite. Thus, the former and the latter can be inferred as high-Mg granites (HMGs) and low-Mg granites (LMGs), respectively. The Sr-Nd-Hf isotopes and geochemical features indicate that the Liemai two‐mica granite, similar to other adjacent HMGs, was derived from partial melting of a thickened lower crust consisting mainly of garnet amphibolite with subordinate metapelites. Although the LMGs show similar Sr-Nd-Hf isotopes to the HMGs, perceptible differences in whole-rock major and trace elements suggest a different evolutionary path. According to recent studies of differentiation processes in silicic magma reservoirs, we proposed that the HMGs represent a congealed crystal mush that was composed of ‘cumulate crystals’ and a trapped interstitial liquid, and the LMGs represent the almost pure liquid that was extracted from the crystal mush. Modeling using the trace elements Sr and Ba shows that the extraction probably occurred when the crystallinity of the mush was ~60–63%, at least for the most evolved LMGs sample. The HMGs corresponds to a residual crystal mush that had a terminal porosity of ~21–25% filled with a trapped interstitial liquid. Underplating of mafic magmas following slab breakoff of the Neo-Tethys oceanic lithosphere caused partial melting of the thickened lower crust (>50 km).